Innovation Strategy With Environment Variable Antesenden Internal, External And Environmental Partnership Strategy For Their Impact On The Sustainable Competitive Advantage(Survey on Small Business in Pangkalpinang city) - . Reniati; Dian Prihardini Wibawa (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Environment faced byentrepreneurstodayhave changed. Therefore, companiesneed to considerinternaland externalenvironmentstosurvive thecompetition. Besidespartneringstrategybecomevery important to doin order to achievesuperiorperformanceandsustainablecompetitive advantage.This studyaimed toanalyzethe influence ofthe internal environment,external environmentandstrategicpartnershipsforinnovation strategyandits impact onSMEsFeaturedsustainablecompetitive advantage. The research methoduseddescriptive and verificationwith a sampleof 48SMEsfeaturedinPangkalpinang citytaken byrandomsampling. The analysis techniqueused isthe Partial Least Square âPath Method. So theexpectedfindingsareas follows:BaseResourcesStrategy, SMEPartnershipStrategy, Innovation StrategyandaModelPolicyforDevelopment ofSMEsin the province ofBangkaBelitung. Results showedinternal environmentto have the mostdominantin influencingsustainablecompetitive advantage, followed by theexternal environmentand innovation strategies. Thepartnershipstrategyhas nota significant effect onsustainablecompetitive advantage, butto theinnovation strategy, strategicpartnerships have apositive effect. In addition tostrategicpartnerships,internal environmentand the external environmentalso affect theinnovation strategyof SMEPangkalpinangcity.